2021
DOI: 10.3390/jcm10092041
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Care Networks in Rehabilitation Care for Patients with Chronic Musculoskeletal Pain: A Systematic Review

Abstract: This systematic review aims to identify what rehabilitation care networks, within primary care or between primary and other health care settings, have been described for patients with chronic musculoskeletal pain, and what their impact is on the Quadruple Aim outcomes (health; health care costs; quality of care experienced by patients; work satisfaction for health care professionals). Studies published between 1 January 1994 and 11 April 2019 were identified in PubMed, CINAHL, Web of Science, and PsycInfo. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 100 publications
(279 reference statements)
1
7
0
Order By: Relevance
“…This suggested that teams in which members (regardless of their profession) favorably communicated with each other and shared goals could achieve sufficient effects of care while reducing related challenges. These results supported those of previous studies that showed that interprofessional collaboration improved the quality of care for users 9,10 . A previous study showed that psychological safety strengthened the relationships among hospital nurses 19 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This suggested that teams in which members (regardless of their profession) favorably communicated with each other and shared goals could achieve sufficient effects of care while reducing related challenges. These results supported those of previous studies that showed that interprofessional collaboration improved the quality of care for users 9,10 . A previous study showed that psychological safety strengthened the relationships among hospital nurses 19 .…”
Section: Discussionsupporting
confidence: 90%
“…These results supported those of previous studies that showed that interprofessional collaboration improved the quality of care for users. 9,10 A previous study showed that psychological safety strengthened the relationships among hospital nurses. 19 In this study, some nurses perceived there to be lower "Difficulty of cooperation among nurses because of differences in attitudes" when cooperation among nurses was stronger, which suggested that psychological safety among nurses strengthened cooperation and decreased the perceived difficulty in cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rehabilitation may be defined as the multi and interdisciplinary management of a person's functioning and health [ 34 , 60 , 68 ]. The interdisciplinary team consists of professionals including physiotherapists (PT), occupational therapists (OT), speech and language pathologists (SLP), clinical psychologists (CP), medical social workers (MSW), registered nurses (RN), medical doctors (MD) working in concert with the patient and family.…”
Section: Introductionmentioning
confidence: 99%